Interaction of a quantum field with a rotating heat bath - Alicki, Robert (2018)
The linear coupling of a rotating heat bath to a quantum field is studied in the framework of the Markovian master equation for the field's non-unitary time evolution. The bath's rotation induces population inversion for the field's low-energy modes. For bosons, this leads to superradiance, an irreversible process in which some of the bath's kinetic energy is extracted by spontaneous and stimulated emission. We find the energy and entropy balance for such systems and apply our results to the theory of black hole radiation. We also comment on how this relates to classical self-oscillations, including shear flow instabilities in hydrodynamics.